EVALUASI EFEKTIVITAS PROGRAM SEMINAR ON EARLY CHILHOOD INSTITUTION, EDUCATION AND DEVELOPMENT (SEED) 2021 PADA GURU PAUD DI KABUPATEN OGAN KOMERING ULU - Firdaus, Guntur; Kartika, Lindawati (Peneliti.net, 2023)
Preschool education, or PAUD, is how early childhood education is carried out in Indonesia for children ages 0 to 6. The shortage of qualified and sufficient early childhood education teachers has hampered the development of early childhood education in Indonesia. A PAUD, or professional development program for early childhood educators, is one remedy. Several parties have arranged a number of training programs, but they are still operating independently and without incorporating all current stakeholders. All academic and governmental stakeholders are included in the training program SEED, which is run by the Management Department of IPB University. This study's objectives were to assess the SEED 2021 program's effectiveness as well as the sustainability implementation and strategy.